Role of the electrolyte in gas formation during the cycling of a Gr//NMC battery as a function of temperature: Solvent, salt, and ionic liquid effect - Raghibi, Mohamed; Xiong, Baokou; Phadke, Satyajit; Anouti, Mérièm (Electrochimica acta, 2020)
The operation of lithium-ion batteries, whether normal or in abusive conditions, is accompanied by the generation of gas in particular during the first cycles. This is intrinsic to the device and is subject to numerous parameters such as the electrode materials used, the electrolyte or even the operating conditions. This generation of gas is harmful: it leads to an increase in the internal pressure of the batteries, raising safety problems. In the present study we propose an original experimental protocol to measure the volume of gas generated during cycling of Gr//NMC full cell in pouch cells systems. We compared the values obtained at two temperatures with 7 different electrolytes formulated with 4 alkylcarbonate solvents (EC, PC, DMC, EMC), two salts (LiPF6 and LiTFSI) and 2 ionic liquids, methyl butyl pyrrolidinium bis (trifluoro-sulfonyl) imide (Pyrr14 TFSI) and methyl tributyl phosphonium bis (trifluoro-sulfonyl) imide (Phos1444 TFSI). The gases generated were identified by GC/MS and the gas solubility (O2, H2) was measured ex-situ. The objective was to discern the respective roles of salts, solvents and ionic liquids on the swelling of the batteries. The results showed that the quantity of gas produced is essentially linked to the formation of the solid electrolyte interphase (SEI) at the first charge. It is greater in the case of LiTFSI compared to LiPF6 (2.8 mL vs 1.9 mL). The quantities of gas were correlated with the solubility of gases in the electrolyte measured for H2 and O2 with and without salt. The LiTFSI result allows a “salting in” effect which physically results in the wilting of the pouch cells and a reduction in the volume of gas during cycling. This phenomenon, attributed to a better solubility of the gases produced in the electrolyte in the presence of this salt, is accentuated with temperature. Lastly, analysis of the gas composition by GC-MS revealed a predominance of CO2 and CH4 gases and confirmed the effect of salt in the quantity and composition of the gas mixture. Ionic liquids and LiTFSI are interesting at high temperatures and for systems subject to high gas generation especially O2, such as transition metal oxide cathodes. [Display omitted]